Zakat Regulation as a Reduction of Income Tax in Indonesia - Aripin Marpaung (Budapest International Research and Critics University, 2020)
Zakat is one part of the rules of social security in Islam, in a deeper and broader scope, which includes aspects of material and spiritual life. Zakat is also a financial, economic, social, political, moral and religious system at the same time. Zakat as a financial and economic system, because it is a specified property tax. Zakat is a financial source of baitul mall in Islam that is continuous. Zakat as a social system, because it functions to save people from various weaknesses, overcome various disasters and accidents, provide humanitarian assistance, who are helping those who do not have, the strong help the weak. Zakat and tax are the material obligations of a citizen of his country and are a source of state income used to finance state expenses and needs. the position of zakat cannot be replaced by taxation. the problem in Indonesia where the majority of the population is Muslim, in addition to being obligatory zakat they are also burdened with various taxes, so that a middle way can be taken,namely reducing the amount of tax by the amount of zakat that has been paid. Thus a taxpayer can still pay obligations as citizens and continue to fulfill their religious obligations.